Case series: long term experience with different types of hypospadias and its correction by single stage procedure - Kumar, Amarendra; Narayan, Chandramohan; Faiz, Nameer (International Surgery Journal, 2018)
Background: Hypospadias is a relatively common congenital defect of the male external genitalia. It is present in approximately 1 in 250 male newborns. Hypospadias, in boys, is defined as an association of three anomalies of the penis: an abnormal ventral opening of the urethral meatus that may be located anywhere from the ventral aspect of the glans penis to the perineum, an abnormal ventral curvature of the penis (chordee), and an abnormal distribution of foreskin with a “hood” present dorsally and deficient foreskin ventrally. Methods: In this study author operated 250 cases of Hypospadias of different types in different age groups during (1992-2017) using MAGPI for glandular, TIP and Flip-flap procedure for distal penile and Ducket Onlay Flap technique for Proximal penile, penoscrotal and perineal Hypospadias. Complicated / Failed Hypospadias was repaired by Trap door technique or Byer’s double tube technique. Results: After the primary repair of Hypospadias fistula was found in 4.5% of patients. Post-operative haemorrhage was seen in 3.2% of patients. Flap Necrosis was found in 8% of patients after Mathieu’s Flip- Flap technique. The success rate of Complicated Hypospadias was quite satisfactory and Meatal Stenosis was seen in 10% of the cases. Over All study has shown superior cosmetic results and one stage repair is cost effective, satisfactory and less psychologically affecting the parents and the patients. Conclusions: MAGPI and its different modifications in the repair for Glandular and Flip-flap or TIP for distal penile in cases of mild or no chordee. Proximal Penile has sufficient Chordee and can be corrected by dorsal plication and urethroplasty by Ducket’s Onlay flap technique. The cost-effectiveness due to single stage repair and its cosmetic results and there least complications prove the efficacy of this protocol. Single stage repair is also beneficial for developing countries like India where the follow-up compliance in the rural patients is extremely poor.